Coastal Haze Pollution, Economic and Financial Performance, and Sustainable Transformation in Coastal Cities - Wang, Dongwu; Li, Jiao (Journal of coastal research, 2020)
Wang, D. and Li, J., 2020. Coastal haze pollution, economic and financial performance, and sustainable transformation in coastal cities. In: Wan, Z. (ed.), Coordinated Sustainable Development in Coastal Areas: Environment and Economy. Journal of Coastal Research, Special Issue No. 109, pp. 1–7. Coconut Creek (Florida), ISSN 0749-0208. In this paper, 76 coastal cities in China are selected as the research objects to analyze the relationship between coastal economic and financial performance and environmental quality. The empirical results show that the increase of per capita output value aggravates the overall pollution situation of the city, and when the financial pressure of the city increases, the overall pollution situation will slow down. Secondly, with the improvement of labor income, the requirements for the improvement of coastal environmental quality will increase and the effect of pollution control and environmental quality improvement will be achieved.